Narratives of an exodus - Elhadj Ould Brahim (L’Année du Maghreb)
This article examines the recent surge of Mauritanian immigration to the United States through the metaphorical lens of lehwyṭ likṣayr (“little short wall”), a Hassaniya expression symbolizing ease and accessibility. Migrants refer to the U.S.–Mexico border as hayṭ Trump (“Trump’s Wall”), which has become a focal point for narratives of resilience and resistance. Using a combination of discourse analysis from social media and ethnographic data gathered from migrants before they encountered hayṭ Trump, this study delves into the factors driving this unprecedented migration wave. Central to this analysis is the concept of the policing of migrants (Del Percio, 2018, p. 239), employed as a symbolic tool by religious authorities, intellectuals, and NGOs in Mauritania. This unifying narrative criminalizes migration while failing to address its structural causes. Despite efforts to marginalize migrants, the study shows how these primarily Bidan (self-identified “white” Arabophone) individuals exercise agency by reshaping the narratives imposed on them, using cultural expressions such as poetry, music, and storytelling to contest the barriers they face. Ultimately, it reveals how Mauritanian migrants navigate and resist both physical and symbolic walls, transforming their journey into an act of defiance that subverts the dominant discourses surrounding migration and power.